Deutung von Orts- und Flurnetzen im Hochland von Mexiko als kultreligiöse Reliktformen altindianischer Besiedlung - Tichy, Franz (ERDKUNDE, 1974)
Through the analysis of field and village plans, in con junction with the measurement of the orientation of ruins and churches of the colonial period, three differently arranged rectangular systems were recognised and delimited in the historically settled basin area of the south east Mexican Highlands. Because of preclassical ruins arranged in the same way, at least two of the three systems can be dated around the time of the birth of Christ. The orientation 17° and 26-28° are solar oriented from an hypothetical observatory mountain. The 17° system is connected with the time of maize sowing in the dry field system. The three systems are thought to be relict forms of a religious cult, and have survived from the time of the early Indian settlement by a people of the Mesoamerican High Culture, because they provided a basis for church building and urban foundation in the early colonial period. A fourth rectangular system exists in the chess-board ground plans of a number of villages which received Franciscan monasteries and are mostly oriented by compass direction. The colonial period brought a number of important changes with the foundation of haciendas, sometimes on the sites of former village settlements, but only seldom altered the ground plan systems.